Subordinating Myth: Latino/a Immigration, Crime, and Exclusion. Issue 2 (4th February 2013) - Longazel, Jamie
Abstract Rhetoric about "crime‐prone immigrants" has contributed to increased enforcement of the U.S.‐Mexico border, the passage of punitive immigration laws, and state and local efforts to make life difficult for new arrivals. Yet scholarly research refutes the notion that immigrants commit more crime. How do we explain this glaring contradiction? By reviewing recent research on immigration, crime, and social control in the context of racial stratification, this article describes the criminalization of Latino/a immigrants in the U.S. as a subordinating myth; that is, a falsity used as part of a larger effort to misallocate material, political, and cultural resources. Four ways in which the criminalization of immigrants contributes to racial exclusion are discussed: the profiting from immigration detention; the political scapegoating of racialized immigrants; the degrading of racialized bodies in enforcement efforts; and the literal control of exploitable populations. The article concludes with a call to develop further our understanding of the relationship between immigration and crime from this critical perspective in order to subordinate the myth of immigrant criminality.